2014
DOI: 10.3390/rs61211956
|View full text |Cite
|
Sign up to set email alerts
|

Automated Extraction of the Archaeological Tops of Qanat Shafts from VHR Imagery in Google Earth

Abstract: Qanats in northern Xinjiang of China provide valuable information for agriculturists and anthropologists who seek fundamental understanding of the distribution of qanat water supply systems with regard to water resource utilization, the development of oasis agriculture, and eventually climate change. Only the tops of qanat shafts (TQSs), indicating the course of the qanats, can be observed from space, and their circular archaeological traces can also be seen in very high resolution imagery in Google Earth. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 55 publications
0
38
0
Order By: Relevance
“…Mapping individual karezes and their recharge zones is easily accomplished using freely available digital maps like Google Earth ( Fig. 3; Luo et al 2014), digital elevation maps and geological maps (USGS 2010; partly shown in Fig. 2).…”
Section: Strategies For Rehabilitating Karezesmentioning
confidence: 99%
“…Mapping individual karezes and their recharge zones is easily accomplished using freely available digital maps like Google Earth ( Fig. 3; Luo et al 2014), digital elevation maps and geological maps (USGS 2010; partly shown in Fig. 2).…”
Section: Strategies For Rehabilitating Karezesmentioning
confidence: 99%
“…; Trathan ; similarly, archeological remote sensing: Luo et al. ). In contrast, the surface characteristics of the HAI are not homogenous and many items in the background appear similar to nests in the aerial imagery, including drab vegetation and senescent plant matter.…”
Section: Introductionmentioning
confidence: 97%
“…Google Earth images have only three bands: red, green, and blue (RGB). Owing to the poor spectral information, there have not been too many ISA or land-cover mapping studies based on Google Earth image, as they are mainly used for small object detection, such as village buildings [18], scattered shrubs [19], ships [20], and qanat shafts [21]. As a free high spatial resolution image data source, Google Earth has a high potential for high resolution ISA mapping.…”
Section: Introductionmentioning
confidence: 99%